The Effect of Corporate Governance, Business Ethics, and Regulatory Compliance on Sustainable Business Performance - Mahmuddin, Mahmuddin; Fauzi, Irsal; Maghfirah, Nur; Siagian, Ade Onny (IJBLE Scientific Publications Community Inc., 2026)
This study examines the effect of corporate governance, business ethics, and regulatory compliance on sustainable business performance. Drawing on agency theory, stakeholder theory, and institutional theory, the study adopts a quantitative research approach using a cross-sectional survey design. Data were collected through structured questionnaires administered to managers and senior executives across selected organizations, resulting in 287 valid responses. Corporate governance, business ethics, and regulatory compliance were measured using established multi-item scales, while sustainable business performance was assessed across economic, social, and environmental dimensions. Data analysis was conducted using descriptive statistics, correlation analysis, and multiple regression techniques. The results reveal that corporate governance, business ethics, and regulatory compliance all have positive and statistically significant effects on sustainable business performance. Among the three predictors, business ethics emerged as the strongest determinant, followed by corporate governance and regulatory compliance. The findings suggest that sustainable business performance is best achieved through an integrated approach that combines effective governance structures, ethical organizational culture, and proactive regulatory compliance. The study contributes to the existing literature by providing empirical evidence on the combined influence of governance, ethics, and compliance on sustainability and offers practical insights for managers and policymakers aiming to enhance long-term organizational performance.